Rhineland exit? - Lans Bovenberg; Coen N. Teulings (Tinbergen Institute, 2007)
We argue in favour of the shareholder model of the firm for three main reasons. First, serving multiple stakeholders leads to ill-defined property rights. What sounds like a fair compromise between stakeholders can easily evolve in a permanent struggle between the stakeholders about the ultimate goal of the company. In many cases, the vague Rhineland principles no longer offer much protection to workers. Second, giving workers a claim on the surplus of the firm raises the cost of capital for investments in jobs, which harms the position of job seekers, including new entrants to the labour market. Third, and most importantly, making shareholders the ultimate owner of the firm provides the best possible diversification of firm-specific risks. Whereas globalisation has increased firm-specific risk by intensifying competition, globalisation of capital markets has also greatly increased the scope for diversification of firm-specific risk. Diversification of this risk on the capital market is an efficient form of social insurance. Reducing the claims of workers on the surplus of the firm can be seen as the next step in the emancipation of workers. Workers derive their security not from the firm that employs them but from the value of their own human capital. In such a world, global trade in corporate control, global competition and creative destruction associated with these developments are more legitimate.Coordination in wage bargaining and collective norms on what is proper compensation play an important role in reducing the claim of workers on the firm's surplus, thereby protecting workers against firm-specific risks. Indeed, in Denmark, workers bear less firm-specific risk than workers in the United States do. Collective action thus has an important role to play. Politicians, however, also face the temptation to please voters and incumbent workers with short-run gains at the expense of exposing workers to firm-specific risks and reducing job creation. This is why corporate governance legislation that gives moral legitimacy to the claim of insiders on the surplus of the firm is damaging.The transition from the Rhineland model (in which management serves the interests of all stakeholders) towards the shareholder model is fraught with difficulties. While society reaps long-run gains in efficiency, in the short run a generation of insiders has to give up their rights without benefiting from increased job creation and higher starting wages. Whereas the claims of older workers on the surplus of a firm may thus have some legitimacy, younger cohorts should be denied such moral claims. These problems require extreme political skill to solve. In particular, they may require some grandfathering provisions or temporary explicit transfers from younger to older generations.
Keywords: E24; G32; G34; 330; wagesetting; optimal risk sharing; employment protection; corporate governance; Lohnbildung; Beschäftigungssicherung; Corporate Governance; Wirtschaftsordnung; Vergleich; Dänemark; Portugal; USA